Society Prizewinner Collection – The Division of Coordination Chemistry of the French Chemical Society. Issue 18 (11th May 2020) - Proust, Anna; Poli, Rinaldo
Abstract : Guest Editors Anna Proust and Rinaldo Poli briefly present the Division of Coordination Chemistry of the French Chemical Society and the annual prize it awards to selected scientists, who are the authors of this Society Prizewinner Collection.